Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.bbmt.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Radiologic Assessment of the Brain after Reduced-Intensity Unrelated Donor Transplantation for Severe Sickle Cell Disease: Blood and Marrow Transplant Clinical Trials Network Study 0601

Abstract: Stroke and cognitive decline are hallmarks of sickle cell disease (SCD). The natural history of SCD predicts progressive loss of 1 IQ point per year attributable to disease-related pathology. Hematopoietic cell transplantation (HCT) is curative by reverting to donor-derived erythropoiesis, but evidence that HCT can positively influence diseaseinduced cognitive decline is lacking. The Sickle Cell Unrelated Transplant Trial prospectively evaluated cognition and brain magnetic resonance imaging (MRI) findings at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
(22 reference statements)
2
21
0
Order By: Relevance
“…In the Baby-Hug trial comparing hydroxyurea to placebo, no difference was found between groups and only a trend toward better cognitive performances was reported in those on hydroxyurea with baseline severe anemia [99]. Following SCT, stabilization with age of cognitive performances has been found [100], but the DREPAGREFFE trial comparing chronic transfusion to HSCT in children with abnormal-TCD history did not find any significant difference in cognitive performances between both groups at the 1 and 3-year follow-up. However, a significantly higher progression of the processing speed index was seen in the transplantation group from 1 to 3 years : 6.1 (12.9) vs. −3.1 (10.5) in the standard-care group, p = 0.02 [80].…”
Section: Who To Consider For Allogeneic Stem Cell Transplantation mentioning
confidence: 99%
“…In the Baby-Hug trial comparing hydroxyurea to placebo, no difference was found between groups and only a trend toward better cognitive performances was reported in those on hydroxyurea with baseline severe anemia [99]. Following SCT, stabilization with age of cognitive performances has been found [100], but the DREPAGREFFE trial comparing chronic transfusion to HSCT in children with abnormal-TCD history did not find any significant difference in cognitive performances between both groups at the 1 and 3-year follow-up. However, a significantly higher progression of the processing speed index was seen in the transplantation group from 1 to 3 years : 6.1 (12.9) vs. −3.1 (10.5) in the standard-care group, p = 0.02 [80].…”
Section: Who To Consider For Allogeneic Stem Cell Transplantation mentioning
confidence: 99%
“…Three published studies to date have assessed the effect of bone marrow transplantation (BMT) on cognition in SCD, and findings show that full-scale IQ remained stable after transplant. [3][4][5] King et al also found that verbal IQ and performance IQ also remain stable. However, these findings are based on very small samples, and replication is necessary across multiple domains of cognition including various transplant approaches.…”
Section: Improvement In Processing Speed Following Haploidentical Bonmentioning
confidence: 95%
“…Few studies have investigated whether therapeutic interventions to prevent cerebral infarction impact progressive neurocognitive benefits in individuals with SCD. Three published studies to date have assessed the effect of bone marrow transplantation (BMT) on cognition in SCD, and findings show that full‐scale IQ remained stable after transplant . King et al also found that verbal IQ and performance IQ also remain stable.…”
Section: Multivariate Analysis Of Different Cognitive Domains Pre‐ Anmentioning
confidence: 99%
“…Patients with severe cerebral vasculopathy or moyamoya disease may be considered for encephaloduroarteriosynangiosis (51). Cerebral blood flow velocity determined by transcranial Doppler velocity (age <16 years) and neurocognitive function may stabilize or improve posttransplant (52) and may be evaluated pre-HCT. Transfusional hemosiderosis and its effect are examined by the quantification of the liver and cardiac iron.…”
Section: Pre-hct Recipient Evaluationsmentioning
confidence: 99%
“…In more recent series, reduced toxicity/intensity (10,13,81) and NMA (18,20,67,103) conditioning regimens have been demonstrated to be safe and effective in ameliorating SCD clinical manifestations (10,13,81). Following HCT, the transcranial Doppler velocity returns to normal; there is a stabilization of organ function, stabilization of full-scale IQ, improved healthrelated QoL (HRQoL), decreased prescriptions of opioid pain medications, and improvement in splenic function (11,13,14,52,55,(104)(105)(106)(107). Adult patients followed in the 2nd year after a successful HCT for SCD, as compared to pre-HCT, and as compared to a group of SCD patients who had not undergone HCT, had significantly lower rates of healthcare utilization and healthcare costs (108).…”
Section: Outcomes Following Hctmentioning
confidence: 99%